Phase stability and distortion in high-entropy oxides. (March 2018) - Anand, G.; Wynn, Alex P.; Handley, Christopher M.; Freeman, Colin L.
Abstract: The present investigation demonstrates how configurational entropy stabilises rock-salt type single phase multi-component solid solution oxides. Classical simulations have been used to extensively sample the configurational landscape of such oxides using both random and genetic algorithm sampling strategies. The thermodynamic properties including the enthalpy and free energy of various oxide mixes have been calculated to show the influence of the chemical identity of the oxides on the phase stability. Additionally, a distance analysis between all the cation-cation and cation-anion pairs has been carried out in order to quantify the distortion in the lattice. The correlation between the multiplicity of cations in such systems with consequent enthalpy and configurational entropy has been enumerated and its relation with emergent distortion has been analysed. Graphical abstract: Image 1